Dark co-fermentation of rice straw and pig manure for biohydrogen production: effects of different inoculum pretreatments and substrate mixing ratio. Issue 28 (19th December 2021) - Chen, Hong; Wu, Jun; Wang, Hong; Zhou, Yaoyu; Xiao, Benyi; Zhou, Lu; Yu, Guanlong; Yang, Min; Xiong, Ying; Wu, Sha
ABSTRACT: Biohydrogen produced from agricultural waste through dark co-fermentation is an increasingly valuable source of renewable energy. Rice straw (RS) and pig manure (PM) are widely available waste products in Asia with complementary levels of carbon and nitrogen that together have a high biohydrogen production potential. However, no research has yet determined the ideal inoculum pretreatment method and mixing ratio for biohydrogen production using these resources. In this study, we tested biohydrogen production using three different inoculum pretreatment methods (acid, alkali and thermal) at five RS/PM ratios (1:0, 5:1, 3:1, 1:1 and 0:1, based on total solids). All three pretreatments promoted biohydrogen production with the increase of bioactivity of biohydrogen-producing organisms (compared with a control group), though acid was clearly superior to thermal or alkali. Using acid pretreatment and RS/PM ratio of 5:1 corresponded with a relatively low N H 4 + -N concentration (655.17 mg/L), a maximal cumulative biohydrogen production of 44.59 mL/g VSadded with a low methane production (<0.1%), a large butyric acid accumulation (1035.30 mg/L) and a biohydrogen conversion rate of 2.12%. The optimal pH for biohydrogen production from co-fermentation of RS and PM ranged from 5.0–5.5. GRAPHICAL ABSTRACT: UF0001